Influence of microphone position in the recording of speech signals - Ludvigsen, Carl (Annual Report of the Institute of Phonetics University of Copenhagen, 1979)
Sound pressure levels of various speech sounds are measured simultaneously at different distances from the mouth. The observed values for low vowels and [s] differ especially close to the mouth from those predicted from the distance law for sound radiation. The variation of sound pressure with distance seems to depend on the speech sound in question. Some consequences hereof are pointed out. The results are compared with calculated values of the sound pressure from a sound source on a rigid sphere. Some of the observed deviations from the distance law seem attributable to the different frequency composition of the speech sounds. However, some of the observations (e.g. the difference between the variation of low and high vowels at positions close to the mouth) cannot be accounted for by the model.